The Effectiveness of Application (Adolescent Thalassemia Self) on the Quality of Life of Children with Thalassemia - Ria Andriani; Burhanudin Basri; Hadi Abdillah; Reni Mulyani (Borneo Scientific Publishing, 2026)
Thalassemia is a chronic hereditary blood disorder that requires lifelong blood transfusions and iron chelation therapy, significantly affecting the physical, emotional, social, and academic functioning of adolescents. These challenges highlight the need for innovative, technology-based interventions to support sustainable self-care. This study aimed to determine the effectiveness of the SETARA (Self-Care Thalassemia Adolescents) application in improving the quality of life among adolescents with thalassemia compared to standard education. A quasi-experimental pre–post design with a control group was conducted involving 34 adolescents aged 12–18 years with transfusion-dependent thalassemia. Participants were equally divided into intervention and control groups (n = 17 each). The intervention group used the SETARA application for 4–8 weeks, while the control group received standard education. Quality of life was measured using the PedsQL Thalassemia Module and analyzed using a paired samples t-test. The results showed a statistically significant improvement in the quality of life in the intervention group (p < 0.001), indicating the effectiveness of the SETARA application. In contrast, the control group did not show a significant change (p = 0.205). In conclusion, the SETARA application is effective in improving the quality of life of adolescents with thalassemia and has the potential to complement standard education and clinical care. It is recommended that adolescents use the application regularly, and healthcare professionals integrate it into patient education and family support programs.